Legal Reforms for Prevention of Custodial Torture in Pakistan - Mahnoor Baig; Zuntiqam Ul Hassan; Dr. Imtiaz Ahmad Khan (Research Journal of Psychology, 2025)
Custodial torture is an evil which is world-wide phenomenon. The custodial torture is also under limelight of basic fundamental rights envisages in constitution. Torture is used to extract evidence from the accused persons which is violation of basic rights like right to life, dignity. Custodial torture might be in police custody or in judicial custody. This research is to identify that how systematic torture carried out by law enforcements agencies under the shadow of investigation and what kind of legal reforms are necessary to prevent custodial torture and humiliating behaviors for the accuse persons. The qualitative methods will be adopted for purpose of collecting data. This research will provide help to legislature to sort out issues regarding torture.